BURNOUT AMONG MUSLIM LECTURER IN MALAYSIA: SINGLE OR MARRIED BETTER? - Wan Nur Ainna Waheda Rozali; Ainuddin Kamaruddin; Nur Yani Che Hussin; Raja Nurul Hafizah Raja Ismail (Journal of Islamic, Social, Economics and Development, 2023)
In January 2020, a new coronavirus epidemic began in Wuhan, China, and now is spreading globally as a pandemic in March 2020. To date, about 123,498 million cases have been reported worldwide and about 2.71 million deaths were reported. This newly discovered pandemic has majorly impacted many things such as education, the economy, and others. Because of this, academician to be affected. Through a survey conducted online in the state of Pahang, Malaysia, this study aims to examine the level of burnout among Muslim lecturer based on marital status in Malaysia . The research used an online questionnaire administered to Muslim lecturers, specifically the Maslach Burnout Inventory in its Bahasa Melayu form. The survey was completed by 303 respondents (N=303) from public and private higher education institutions around the country. The result of the study showed that 49% of the respondents reported having moderate emotional exhaustion, whereas just 19% reported having low emotional exhaustion. In terms of depersonalization, 34% of respondents reported low levels, 52% reported moderate levels, and 14% of Muslim lecturer reported high levels. Next, based on marital status, 79% of married lecturers are at a high level compared to only 18% of single lecturers and 3% of widow or widower lecturers. In the depersonalization subscale, 79% of married lecturers are at a high level, while 17% of single lecturers are at moderate level and 3% of widow or widower lecturers are at low level. As for the third subscale in the Maslach Burnout Inventory, which is personal accomplishment, the data shows that 16% of single lecturers and 4% of widow or widower lecturers at a high level of reduced personal accomplishment. Meanwhile, the majority of married lecturers, around 81%, are found to be at a low level in terms of personal accomplishment. Hence, this study is anticipated to assist relevant authorities in planning interventions to address burnout among lecturers.